Analysis of the Implementation of Single Identity Number as an Effort Harmonization of Population, Law, Administration and Taxation in Indonesia - Harnaeni, Nani; Suwitri, Sri; Yuniningsih, Tri; Lituhayu, Dyah (Yayasan Mentari Madani, 2026)
The implementation of the Single Identity Number (SIN) in Indonesia represents a strategic step to integrate the legal framework of population administration with tax administration. This study aims to analyze the policies, legal foundations, and challenges of implementing SIN as an instrument to strengthen public administration governance and increase state revenue. The research applies a normative legal method through literature reviews of regulations, government policies, and scholarly works related to the integration of population and taxation data. The findings indicate that SIN plays a significant role in preventing data duplication, improving the accuracy of taxpayer information, and strengthening inter-agency coordination, particularly between Dukcapil and the Directorate General of Taxes. Nevertheless, several challenges persist, including technological infrastructure limitations, personal data protection issues, and bureaucratic resistance. In conclusion, the successful implementation of SIN requires regulatory reforms, strengthened cybersecurity, and enhanced digital literacy, enabling it to serve as a pillar of legal harmonization and public administration in the fields of population and taxation